2024
DOI: 10.1001/jamaoncol.2023.6789
|View full text |Cite
|
Sign up to set email alerts
|

Pegargiminase Plus First-Line Chemotherapy in Patients With Nonepithelioid Pleural Mesothelioma

Peter W. Szlosarek,
Benjamin C. Creelan,
Thomas Sarkodie
et al.

Abstract: ImportanceArginine deprivation using ADI-PEG20 (pegargiminase) combined with chemotherapy is untested in a randomized study among patients with cancer. ATOMIC-Meso (ADI-PEG20 Targeting of Malignancies Induces Cytotoxicity-Mesothelioma) is a pivotal trial comparing standard first-line chemotherapy plus pegargiminase or placebo in patients with nonepithelioid pleural mesothelioma.ObjectiveTo determine the effect of pegargiminase-based chemotherapy on survival in nonepithelioid pleural mesothelioma, an arginine-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 52 publications
0
0
1
Order By: Relevance
“…Unsurprisingly, these tumors are exquisitely sensitive to arginine depletion, leading to clinical trials seeking to exploit this metabolic vulnerability by using an arginine deiminase enzyme therapy (ADI-PEG20) to catabolize circulating arginine into citrulline and the ammonium ion 22 . A recent phase II clinical trial in mesothelioma showed increased overall survival in patients treated with ADI-PEG20, although ASS1 expression was not a patient-specific variable in this study 23 . Re-expression of ASS1 could enable tumor cells to escape arginine-depletion treatment by utilizing citrulline 24 .…”
Section: Introductioncontrasting
confidence: 57%
“…Unsurprisingly, these tumors are exquisitely sensitive to arginine depletion, leading to clinical trials seeking to exploit this metabolic vulnerability by using an arginine deiminase enzyme therapy (ADI-PEG20) to catabolize circulating arginine into citrulline and the ammonium ion 22 . A recent phase II clinical trial in mesothelioma showed increased overall survival in patients treated with ADI-PEG20, although ASS1 expression was not a patient-specific variable in this study 23 . Re-expression of ASS1 could enable tumor cells to escape arginine-depletion treatment by utilizing citrulline 24 .…”
Section: Introductioncontrasting
confidence: 57%